Prospective study in bullous pemphigoid: association of high serum anti‐BP180 IgG levels with increased mortality and reduced Karnofsky score. (1st October 2018) - Holtsche, M.M.; Goletz, S.; van Beek, N.; Zillikens, D.; Benoit, S.; Harman, K.; Walton, S.; English, J.; Sticherling, M.; Chapman, A.; Levell, N.J.; Groves, R.; et al.
Summary: Background: Bullous pemphigoid (BP) is a subepidermal blistering disease characterized by autoantibodies against the two hemidesmosomal proteins, BP180 (type XVII collagen) and BP230. The multicentre prospective BLISTER (Bullous Pemphigoid Steroids and Tetracyclines) trial randomized 253 patients with BP to compare the benefits and harms between initial treatment with doxycycline or prednisolone. Objectives: To analyse distinct autoantibody profiles for the prediction of the disease course in a well‐characterized cohort of BP sera. Methods: One hundred and forty‐three patients of the BLISTER trial consented to participate in this serological study. Sera taken at baseline were analysed by (i) indirect immunofluorescence, (ii) anti‐BP180 NC16A (16th noncollagenous domain) and anti‐BP230 enzyme‐linked immunosorbent assay and (iii) immunoblotting with various substrates. Results were then linked with clinical parameters including age, Karnofsky score, number of blisters, related adverse events and mortality. Results: Disease activity correlated with immunoglobulin (Ig)G anti‐BP180 levels but not with levels of anti‐BP230 IgG and anti‐BP180 IgE. High levels of both anti‐BP180 IgG and anti‐BP230 IgG were associated with a low Karnofsky score. The presence of anti‐BP230 IgG was more frequent in older patients. Those with higher total IgE serum levels suffered from fewer adverse events. Higher IgG anti‐BP180 levels were associated with an increased 1‐year mortality rate. Conclusions: Analysis of the autoantibody profile is not only of diagnostic relevance but may also be helpful in predicting the course of the disease.